Reconciling Archean organic-rich mudrocks with low primary productivity before the Great Oxygenation Event - Noam Lotem; Birger Rasmussen; Jian-Wei Zi; Sarah S. Zeichner; Theodore M. Present; Yinon M. Bar-On; Woodward W. Fischer (Proceedings of the National Academy of Sciences, 2025)
The organic carbon content of ancient rocks provides a fundamental record of the biosphere on early Earth. For over 50 y, the high organic content of Archean (>2.5 Ga) mudrocks has puzzled geologists and evolutionary biologists, because high biological primary productivity was unexpected for the nascent biosphere before the rise of O 2 . Here, we took a different approach to resolve this apparent paradox, by studying the accumulation rates of Archean organic-rich mudrocks. We evaluated the sedimentation rates of three sections of the Mount McRae Shale and Jeerinah Formation (2.68 to 2.48 Ga, Pilbara Craton, Australia) with new and recently published U–Pb zircon ages from intraformational ash beds. For comparison, we compiled Phanerozoic (<500 Ma) data from comparable depositional settings and developed an idealized model that considers the sedimentation rates for predicting rock organic content. We found that organic-rich Archean mudrocks were deposited under exceptionally low sedimentation rates (~1 m/Ma), in sharp contrast to organic-rich rocks from the Phanerozoic Eon (10 to 100 m/Ma). Constrained by observations, model results indicated that the Archean data reflect low primary productivity (~100-fold lower than during the Phanerozoic) and enhanced preservation under anoxic conditions, with the principal control on organic carbon content provided by dilution with inorganic sediment. Thus, the high organic carbon content which is typically attributed to high productivity instead reflects slow accumulation, high preservation, and minimal inorganic dilution—reconciling the geological evidence with a slow carbon cycle cadence during Archean time.